2016
DOI: 10.15171/jcvtr.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Association of ghrelin with cardiometabolic risk factors in Iranian adolescents: the CASPIAN-III study

Abstract: Introduction: Current evidence suggests that ghrelin could contribute to the development of metabolic syndrome (MetS) in adults, but limited experience exists in adolescents. This study aims to explore the association of ghrelin levels with the MetS components among Iranian adolescents. Methods: In this case-control study, 32 adolescents with MetS and 148 healthy controls were selected randomly from the childhood and Adolescence Surveillance and Prevention of Adult Non communicable disease (CASPIAN-III) study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
4
4
0
Order By: Relevance
“…This is in agreement with the results of previously published studies, proving a compensatory decrease in ghrelin when adipose tissue increases [14,24]. However, some previous studies in children found no correlation between ghrelin and obesity-related hypertension, a correlation that was recently shown in adults [15,25]. In addition, our finding of the role of ghrelin in normal weight hypertension has not been found in any previous studies in children.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the results of previously published studies, proving a compensatory decrease in ghrelin when adipose tissue increases [14,24]. However, some previous studies in children found no correlation between ghrelin and obesity-related hypertension, a correlation that was recently shown in adults [15,25]. In addition, our finding of the role of ghrelin in normal weight hypertension has not been found in any previous studies in children.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we confirmed previous research proving its role in obesity [26,27]. All the analyzed groups had a statistically significant positive correlation between leptin and BMI and a negative correlation between ghrelin and adiponectin and BMI, which are in accordance with earlier studies, thus confirming their potential for the determination of the obesity risk [8,15,26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2016, 45 and partially in agreement with the results of a study conducted by Stepien et al, in Poland, which revealed a non-significant positive correlation with WHR in insulin-sensitive obese patients. However, in the insulin-resistant group of Stepien's study, ghrelin was not significantly correlated negatively with WHR.…”
Section: Discussionsupporting
confidence: 91%
“…It is associated with a 2-fold increase in risk of cardiovascular disease (CVD), CVD mortality, and stroke, and a 1.5-fold increase in risk of all-cause mortality [ 7 – 9 ]. The prevalence of metabolic syndrome is increasing worldwide because of underlying increase in prevalence of obesity; the Third National Health and Nutrition Examination Survey (NHANES III) reported an alarming unadjusted and age-adjusted prevalence of the metabolic syndrome of 21.8% and 23.7%, respectively [ 10 , 11 ]. In Iran according to the results of Tehran Lipid and Glucose Study (TLGS), 33.7% of adults aged ≥20 years old were suffering from metabolic syndrome [ 12 ].…”
Section: Backgroundsmentioning
confidence: 99%